2016
DOI: 10.4208/nmtma.2016.y14014
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Krylov Subspace Method for Solving Large and Sparse Linear System of Equations

Abstract: Most current prevalent iterative methods can be classified into the so-called extended Krylov subspace methods, a class of iterative methods which do not fall into this category are also proposed in this paper. Comparing with traditional Krylov subspace methods which always depend on the matrixvector multiplication with a fixed matrix, the newly introduced methods(the so-called (progressively) accumulated projection methods, or AP (PAP) for short) use a projection matrix which varies in every iteration to form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Algorithm 1 (accumulated projection process-AP) The following procedure produces an approximate vector p to the solution vector x which satisfies Ax = b. This algorithm formed the basis of some more efficient solvers for linear system of equations such as SAP and MSAP and APAP methods introduced in [15] and [14]. It is observed that these methods seem to be more efficient than regular Krylov subspace methods in case of large scale systems in some situation.…”
Section: Principle Of Ap Techniquementioning
confidence: 99%
See 4 more Smart Citations
“…Algorithm 1 (accumulated projection process-AP) The following procedure produces an approximate vector p to the solution vector x which satisfies Ax = b. This algorithm formed the basis of some more efficient solvers for linear system of equations such as SAP and MSAP and APAP methods introduced in [15] and [14]. It is observed that these methods seem to be more efficient than regular Krylov subspace methods in case of large scale systems in some situation.…”
Section: Principle Of Ap Techniquementioning
confidence: 99%
“…These type of methods rely on successive projections over subspaces of R n , which produce a sequence of projection vectors with a monotonically increasing Euclidean norms. Unlike the well-known row-projection technique which can be shown as a traditional stationary iterative methods [7], the AP methods proposed in [14] do not involve matrix-vector multiplications with any fixed matrices and fixed vectors. Equipped with some accelerating technique, the AP methods exhibit some superior behavior than traditional extended Krylov subspace methods [14] in some cases.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations